Литовсько-польська доба в археології України - Моця, О.П. (Археологія, 2017)
У роботі аналізується стан вивчення археологічних пам’яток часів пізнього середньовіччя, котрі розташовані у різних частинах сучасної України (в першу чергу — це укріплені поселення), а також деякі категорії знахідок, що нині найкраще представлені в колекціях (зброя, кераміка та ін.). The period from the 14th to the 17th century had gone down in history of Ukraine as a period when the majority of autochthonous population belonged to foreign state formations: Duchy of Lithuania and later Polish-Lithuanian Commonwealth. In both cases, upper ten of local community switched side of the new masters and gained corresponding benefits. However, in this case, we are interested in changes in material culture which are represented in corresponding archaeological base. First of all, the changes became apparent in city and castle building, which not only preserved Ancient Rus architectural traditions, namely usage of wood, the main local building material, but also in certain extent borrowed the Western and Central European experience in stone usage in new fortifications construction. New city centres also appeared in many cities, though the areas of old citadels were often used. Different tendencies were used in different regions, according to variations in their ecologic peculiarities. The main material innovations exhibit fire-arms arrival and usage: cannon at first, then rifles which gradually displaced old examples, first of all, bows and arrows. Pottery was developing rapidly, although pre-Mongolian forms often appeared in various regions. Glassware production had been also intensively developing since the 15th century. Nevertheless, on a whole, it should be stated that archaeological monuments of this period are studied insufficiently, and the historians know about it only from the written sources, of both home, and foreign origin. ХІV—ХVІ в. представлены в истории Украины как времена вхождения большей части автохтонного населения в состав соседних государственных образований — сначала Великого княжества Литовского, а затем Речи Посполитой. В обеих случаях социальная верхушка местного общества переходила на сторону новых господ и получала из этого соответствующие выгоды. Нас же интересуют изменения в материальной культуре, которые представлены в соответствующем археологическом материале. В первую очередь, они нашли проявление в городском и замковом строительстве, которое не только сохранило древнерусские архитектурные традиции (использование дерева, основного местного строительного материала), но и в какой-то мере восприняло опыт Западной и Центральной Европы в части применения камня при возведении новых укреплений. Появились и новые центры во многих городах, хотя часто использовались и территории старых детинцев. Разные тенденции развивались в разных регионах, что объясняется и различиями в их экологических особенностях. В материальном плане основные новации характеризуются появлением и использованием огнестрельного оружия — сначала пушек, а затем и ружей, которые постепенно вытесняли старые образцы (в первую очередь лук и стрелы). Стремительно шло развитие гончарного ремесла, хотя домонгольские формы часто проявлялись в разных районах. Начиная с ХV в. интенсивно развивается и производство стеклянных изделий. В целом следует констатировать недостаточное изучение археологических памятников данного периода, который известен историкам, в первую очередь, по письменным памятникам.